ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI DEEP BACK MASSAGE UNTUK MENGURANGI NYERI PERSALINAN KALA I FASE AKTIF DI RUMAH SAKIT BHAYANGKARA TK. I RADEN SAID SUKANTO KRAMAT JATI JAKARTA TIMUR - Gita Ekawati (2022)
In the first stage of the active phase of labor, the pain will be felt most dominantly by the mother, the mother often complains of pain and severe contractions to the feeling of wanting to defecate during the first stage of the active phase of labor. Pain in labor can be caused by many things, one of which is the pressure that occurs on the nerve endings between the muscle fibers of the corpus fundus of the uterus. Pain during labor can be treated pharmacologically and non-pharmacologically. Non-pharmacological methods that can be used to reduce pain during labor are massage. The purpose of this study was to determine whether the deep back massage method can reduce labor pain in the first stage of the active phase. The method used in this research is a case study with the application of evidence based nursing in nursing care for two mothers who are entering the first stage of active labor. The instrument used to measure pain intensity was the Numeric Rating Scale (NRS). The results of this study showed that there was a decrease in pain intensity after a deep back massage was carried out for 3 times every hour when the mother felt contractions. In the first patient, the pain scale decreased from a scale of 8-9 (severe pain) to a scale of 6-7 (moderate-severe pain). In the second patient the pain scale also decreased from 6-7 (moderate-severe pain) to 4-5 (moderate pain). The conclusion of this study is that the deep back massage method can reduce labor pain in the active phase of the first stage of labor. Keywords: Deep Back Massage, Labor, Non-pharmacological intervention, Pain